Catalytic Cracking of Heavy Aromatics and Polycyclic Aromatic Hydrocarbons over Fluidized Catalytic Cracking Catalysts - Pujro Tarquino, Richard Alfonzo (2015)
The distribution of products in the range of gasoline and middle distillates cuts obtained in the catalytic cracking of heavy aromatics and polycyclic aromatic hydrocarbons over a FCC catalyst was studied. 1-Phenyloctane, biphenyl, fluorene, 9,10-dihydrophenanthrene, naphthalene, phenanthrene, pyrene and benz[a]anthracene were used as model compounds of alkylaromatic, naphthenic-aromatic and polyaromatic hydrocarbons which are present in VGO and residual feedstocks in the FCC process. The catalyst was used in its fresh and equilibrium forms at 450 ºC in a CREC Riser Simulator reactor with reaction times from 2 to 6 s. Thermal cracking reactions overwhelm the catalytic conversion of naphthenic-aromatic compounds such as fluorene and 9,10-dihydrophenanthrene. Under the same conditions, the fresh catalyst was more active than the equilibrium catalyst. The alkylaromatic, naphthenicaromatic and polyaromatic hydrocarbons, showed catalytic conversions which increased,were relatively stable and decreased, respectively, as a function of reaction time. The distribution of products suggested that most important reactions were thermal dehydrogenation, hydrogen transfer, ring opening, cracking and condensation. It was shown that all the model compounds are cracked, yielding particularly benzene in the gasoline range and coke.